Effect of temperature treatment on the optical characterization of ZnO-Bi2O3-TiO2 varistor ceramics. - Sabri, M.G.M.; Zakaria, Azmi; Rizwan, Zahid; Mohamed Kamari, Halimah; Hashim, Mansor; Zaid, M.H.M. (Academic Journals, 2011)
The optical band-gap energy (Eg) is an important feature of semiconductors which determines their applications in optoelectronics. So, it is necessary to investigate the electronic states of ceramic ZnO and effect of doped impurities at different processing conditions. Eg of the ceramic ZnO + xBi2O3 + xTiO2 where x = 0.5 mol%, was determined using UV-Vis spectrophotometer. The samples was prepared using solid-state route and sintered at the sintering temperatures from 1140 to 1260°C for 45 min in open air. Eg was decreased with increase of sintering temperature. XRD analysis indicates that there is hexagonal ZnO and few small peaks of inter granular layers of secondary phases, namely, Bi4Ti3O12 and Zn2Ti3O8. The relative density of the sintered ceramics decreased and the average grain size increased with the increase of sintering temperature. The variation of sintering temperatures and XRD findings are correlated with the UV-Vis spectrophotometer results of ZnO doped with 0.5 mol% of Bi2O3 and TiO2 due to the formation of interface states at all sintering temperatures.